Efficacia ed efficienza della pubblica amministrazione Effektivität und Effizienz der öffentlichen Verwaltung - Baroncelli, Stefania (bu,press, 2015)
The book addresses the issue of the good performance of public administration using an interdisciplinary approach (legal, political, corporate, and economic). The concepts of efficiency and effectiveness have been defined in the field of business sciences, but have had a much wider impact. An efficient and effective administrative system, in fact, affects the system of values that are the basis of our society, since it makes it possible for citizens to concretely enjoy the services that are recognized by the regulatory system. This requirement appears even more meaningful in Italy, where the principle of so-called "substantial" equality is recognized by the Constitution.; Il libro affronta la questione del buon andamento della pubblica amministrazione usando un approccio interdisciplinare (giuridico, politologico, aziendalistico, ed economico). I concetti di efficienza ed efficacia sono stati definiti nell'ambito delle scienze aziendalistiche, ma hanno avuto un impatto ben più ampio. Un sistema amministrativo efficiente ed efficace, infatti, incide sul sistema di valori che sono a base della nostra società, poiché rende possibile ai cittadini fruire concretamente dei servizi che sono loro riconosciuti dall'ordinamento normativo. Tale esigenza appare ancora più pregnante in Italia, ove il principio di eguaglianza "sostanziale" è riconosciuto dalla Costituzione.